MINAT PADA PROFESI GURU, SEMANGAT KERJA DAN KREATIVITAS GURU TAMAN KANAK-KANAK - Ninik Yuliani; Niken Titi Pratitis (University of Merdeka Malang, 2013)
This research aims to find out the relationship between the interest in the profession of the teacher and the teacher's morale with the creativity of the kindergarten teacher. The subject of research is the kindergarten teachers se-Gampengrejo Regency Kediri Subdistrict totaling 108 men from 32 schools kindergartens in the area. Research sample amounted to 108 people. Data retrieval using three questionnaires each interest in the profession of teachers to gauge the extent of the respondent's interest in the profession of the teacher and the morale of teachers to gauge the extent of the respondent's morale after becoming a teacher as well as the creativity of teachers to gauge how big the creativity of teachers by having their interest to become a teacher and their morale becomes a teacher. To use data analysis regression analysis with two predictors (variables X1 and X2) and one kriterium (variable Y). The results showed that 1) interest in the profession theacher and Creativity kindergarten correlates positively and significantly. Thus the first hypothesis of this research is acceptable. 2) teacher morale and creativity kindergarten correlates positively and significantly. Thus the second hypothesis of this research, can be accepted. 3) interest in the profession of teachers and teacher morale with the creativity of teachers kindergarten is significant. Thus the third hypothesis of this research, can be accepted. While interest in the profession and teacher morale contributed effectively amounted to 40.1%, rest of 59,9% were other factors that proved more influential to the creativity of teachers but not examined in this study.